Credit unions: theory and practice - Dublin, Jack. (Detroit : Wayne State University Press, 1971)
The book is meant to provoke discussion on how the people can be manager to their money and investment.
Bibliography: p. 179-182.
rpm 24/01/2019
Loans
Keywords: Credit unions